Gene frequency and haplotype analysis of HLA class I in patients with simple renal cysts - Al-kaisi, Aroub A.R; Mousawy, Khalida M.; Rifat, Usama N. (AL-Kindy College Medical Journal, 2015)
Background: The study of human leukocytes (HLA) alleles, and haplotype frequencies within populations provide an important source of information for anthropological investigation, organ and hematopoietic stem cell transplantation as well as disease association, certain diseases showed association with specific alleles specially those of known or suspected hereditary origin or immunological basis, whether simple renal cyst is congenital or acquired is still unclear and need to be investigated.Objectives: To study the genetic aspect of simple renal cysts by detecting the gene frequency and the haplotype of HLA class I of patients with simple renal cysts, and to find the presence of these cysts in other family members.Method: Thirty patients with simple renal cysts who were attending the outpatient clinic of urosurgery in the medical city were tested for HLA class I antigen using the microlymphocytotoxicity technique, in the period from February to June 2004 compared to 50 unrelated apparently healthy individuals. Gene frequency were calculated using square root formula (g=1-√1-f), full history were taken including the family history.Results: Certain gene frequencies were higher in the patients group than in the controls, yet not reached to a statistical significant level. No haplotype association with simple renal cysts was detected in this study; family history was detected in two patients which were proved by ultrasound examination.Conclusion: Increasing the sample size may contribute to best results regarding gene frequency, haplotype and family study.Key words: Gene frequency, Haplotype, Human Leukocyte Antigens.